2015
DOI: 10.1007/s00062-015-0420-0
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Findings of a Leiomyosarcoma of the Thoracic Spine: A Case Report

Abstract: We report a case of leiomyosarcoma of the thoracic spine. Primary leiomyosarcoma is a malignant connective tissue tumor originating from smooth muscle cells. Leiomyosarcoma frequently occurs in the uterus, retroperitoneal space, gastrointestinal tract, and deep soft tissues; primary leiomyosarcoma of the bone is rare. The MR imaging including intravoxel incoherent motion (IVIM) imaging findings of the current case indicated a low diffusion coefficient and high blood flow, which were in concurrence with high ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Primary paraspinal cervical [5] and thoracic leiomyosarcoma [14] have also been described. A primary vertebral location is extremely rare and few cases have been described in a spinal location [2] , [3] , [15] , [16] , [17] , [18] , [19] , [20] , [21] with thoracic predominance and mostly in female s , as in our case.…”
Section: Discussionsupporting
confidence: 46%
“…Primary paraspinal cervical [5] and thoracic leiomyosarcoma [14] have also been described. A primary vertebral location is extremely rare and few cases have been described in a spinal location [2] , [3] , [15] , [16] , [17] , [18] , [19] , [20] , [21] with thoracic predominance and mostly in female s , as in our case.…”
Section: Discussionsupporting
confidence: 46%
“…This prompted us to include the entire postoperative bed during radiotherapy planning. Another decision we took in the management of our patient was to limit the dose to 45 Gy, which is different from Tahara et al ,4 who prescribed 70 Gy. Though they also used intensity-modulated radiotherapy, it would be difficult to limit the dose received by the spinal cord to <50 Gy, which is the threshold above which radiation myelopathy would ensue 27.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, a leiomyosarcoma arising de novo from the vertebra is exceedingly rare and so far only nine cases have been reported 3 4. Owing to its rarity, its management is not clearly defined and most cases have been managed with surgery and/or radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry studies are the important investigation to confirm the diagnosis of leiomyosarcoma, especially in differentially diagnoses from other type of carcinomas. From the previous studies, primary leiomyosarcoma of the spine have been reported only 12 cases (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). This case was the 13 th case, which summarized in the Table 1.…”
Section: A B Cmentioning
confidence: 99%